PROBLEM SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN SOLVING HOTS QUESTIONS - Martha, Cut Wira Sukma; Maimunah, Maimunah; Roza, Yenita (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2022)
In the 21st Century Learning, students are encouraged to be more creative in solving mathematical problems that lead to the High Order Thinking Skill (HOTS) level of thinking. The ability to solve problems is the ability to reason, understand problems, plan strategies, carry out procedures in solving problems, and draw conclusions. This study aimed to analyze students' mathematical problem-solving skills in solving HOTS questions. It is qualitative research with a descriptive method. The subjects of this research were 15 7th grade class students of Public Junior High School 39 Pekanbaru. The data collection method used was a test technique using a test instrument consisting of 2 HOTS questions of mathematical problem-solving ability and using the method of independent interviews to research subjects. The data collected was then analyzed through 3 stages: data reduction, data presentation, and conclusion. The results showed that 3 students had problem-solving skills, 8 had moderate problem-solving skills, and 4 had low problem-solving skills. Based on student self-tests and interviews, the seventh-grade Public Junior High School 39 Pekanbaru students average have moderate mathematical problem-solving abilities. Based on the results of the study it can be concluded that students can answer HOTS questions quite well in arithmetic material. each category of students has abilities and deficiencies in answering HOTS questions. From the results of this study, the teacher's role is very important to familiarize students with solving HOTS questions and creating learning innovations. By familiarizing students with solving problems in learning mathematics, students will not only be able to solve the questions given but also solve problems in everyday life